1985
DOI: 10.1007/bf00923261
|View full text |Cite
|
Sign up to set email alerts
|

Recent stressful life events and young children's school adjustment

Abstract: A group of 211 first-to fourth-grade children who had experienced one or more recent stressful life events were compared to a demographically matched sample of 211 children who had not experienced such events on measures of school adjustment problems and competencies. Stressful life events were found to be associated with the presence of more serious school adjustment problems and fewer competencies. Those associations were strongest for children who had experienced multiple recent stressful events. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 24 publications
2
29
0
1
Order By: Relevance
“…In a related vein, Rutter (1983) has suggested that the negative psychological effects of experiencing many SLE-Cs may be more neady multiplicative than additive. That view has recent empirical support (Brown & Cowen, 1989;Sterling, Cowen, Weissberg, Lotyczewski, & Boike, 1985). Given the evidence from these related lines of research that heavy exposure to life stress places children at serious risk for significant adjustment problems, the study of resilient outcomes under such circumstances can yield useful information for prevention.…”
Section: Life Stressors Adjustment and The Resilience Processmentioning
confidence: 94%
“…In a related vein, Rutter (1983) has suggested that the negative psychological effects of experiencing many SLE-Cs may be more neady multiplicative than additive. That view has recent empirical support (Brown & Cowen, 1989;Sterling, Cowen, Weissberg, Lotyczewski, & Boike, 1985). Given the evidence from these related lines of research that heavy exposure to life stress places children at serious risk for significant adjustment problems, the study of resilient outcomes under such circumstances can yield useful information for prevention.…”
Section: Life Stressors Adjustment and The Resilience Processmentioning
confidence: 94%
“…Exposure to multiple, chronic SLE-Cs is thought to increase such negative effects multiplicatively (Rutter, 1979;Sterling, Cowen, Weissberg, Lotyczewski, & Boike, 1985). Studies of risk and resilience have sought to document the effects of stress, as well as protective factors, and to identify processes and pathways that shape stress-affected and stress-resilient outcomes (Cicchetti & Garmezy, 1993;Cowen et al, 1990;Masten, 1989).…”
Section: The Impact Of Stress On Childrenmentioning
confidence: 98%
“…These stressful life events traditionally have been viewed as contributing to adolescent emotional and behavioral problems (Sterling, Cowen, Weissberg, Lotyczewski, & Boike, 1985). Nevertheless, the inconsistency of the empirical findings on the relationship between stressful events and adolescent problems (Burt, Cohen, & Bjorck, 1988;Cohen, Burt, & Bjorck 1987;Swearingen & Cohen, 1985) has led researchers to explore the variables (e.g., social support) that may moderate the sometimes deleterious effects of stressful life events.…”
mentioning
confidence: 99%